Kontribusi Ibu Rumah Tangga Pada Usaha Anyaman Purun Terhadap Peningkatan Pendapatan Keluarga Di Kampung Purun Kelurahan Palam Kota Banjarbaru - Mahfuza Fatmaria; Ari Jumadi Kirnadi; Yarna Hasiani (Fakultas Pertanian UVAYA Banjarmasin, 2023)
The purpose of this study was to determine the technique of making purun plaiting, to determine the cost, revenue, income, and contribution of income from the purun plaiting business by housewives in Kampung Purun, Palam Village, Banjarbaru City. This research was conducted from February to April 2023. This research used survey method. The sample determination was done by Accidental Sampling. The results of this study showed that the making of woven purun includes: purun collection, purun drying, purun pounding, purun coloring, making patterns, weaving, and selling. The average cost incurred in conducting purun weaving business amounted to Rp. 874,250, revenue amounted to Rp. 1,521,600, purun weaving business income amounted to Rp. 1,283,350. The contribution of woven purun business amounted to 44.51%, which means that the contribution of woven purun business is included in the low category, although the low contribution value can still help the economy in the household